2017
DOI: 10.1186/s40623-017-0717-0
|View full text |Cite
|
Sign up to set email alerts
|

Sintering polycrystalline olivine and polycrystalline clinopyroxene containing trace amount of graphite from natural crystals

Abstract: Graphite-bearing polycrystalline olivine and polycrystalline clinopyroxene with submicron to micron grain size were successfully sintered from a single crystal of naturally occurring olivine ). The milled powders of both these crystals were sintered under argon gas flow at temperatures ranging from 1130 to 1350 °C for 2 h. As the sintering temperature increased, the average grain size of olivine increased from 0.2 to 1.4 µm and that of clinopyroxene increased from 0.1 to 2.4 µm. The porosity of sintered samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Therefore, the orthorhombic system of crystals can be transformed into an isotropic symmetry based on the averaging scheme and assuming the isotropic space distribution of each component for the application to validate our theoretical predictions. Experimental studies on polycrystalline olivines show that temperature has little influence on the porosity (Liebermann, 1972), even below 5% at 1300°C (Tsubokawa & Ishikawa, 2017). Figures 1a–1d and 2a–2d contrast the conventional and Padé‐approximant‐based thermoelastic constants with temperatures for the experimental data of polycrystalline RAM and OLA samples in Tables 1 and 2, respectively.…”
Section: Experimental Samples and Resultsmentioning
confidence: 99%
“…Therefore, the orthorhombic system of crystals can be transformed into an isotropic symmetry based on the averaging scheme and assuming the isotropic space distribution of each component for the application to validate our theoretical predictions. Experimental studies on polycrystalline olivines show that temperature has little influence on the porosity (Liebermann, 1972), even below 5% at 1300°C (Tsubokawa & Ishikawa, 2017). Figures 1a–1d and 2a–2d contrast the conventional and Padé‐approximant‐based thermoelastic constants with temperatures for the experimental data of polycrystalline RAM and OLA samples in Tables 1 and 2, respectively.…”
Section: Experimental Samples and Resultsmentioning
confidence: 99%
“…They found that an elastic matrix model is preferable to a Newtonian viscous model for analyzing the stresses involved in microboudinage of columnar tourmaline grains within the quartz matrix of the metamorphic tectonite. Tsubokawa and Ishikawa (2017) reported on the preparation of submicron polycrystalline olivine and clinopyroxene by sintering. Incorporation of trace amounts of graphite allows experimental investigations into the influence of graphite on mantle rheology and seismic velocity.…”
mentioning
confidence: 99%
“…Numerous previous studies have synthesized Mg-Fe olivine. (Brindley and Hayami, 1965;Hanson et al, 1991;Mitchel et al, 1998;Ito et al, 2003;Ando et al, 2007;Ni et al, 2007;Tsubokawa and Ishikawa, 2017;Wang et al, 2017). Generally, solid-state reactions have been used for a long time now to synthesize forsterite (Mg2SiO4) crystals using MgO and SiO2 powder (Brindley and Hayami, 1965).…”
Section: A C C E P T E D I N J M P S P R E -P R O O Fmentioning
confidence: 99%